Compartment-specific pH monitoring in Bacillus subtilis using fluorescent sensor proteins: a tool to analyze the antibacterial effect of weak organic acids - van Beilen, Johan W.; Brul, Stanley (Frontiers in Microbiology, 2013)
The internal pH (pHi) of a living cell is one of its most important physiological parameters. To monitor the pH inside B. subtilis during various stages of its life cycle, we constructed an improved version (IpHluorin) of the ratiometric, pH-sensitive fluorescent protein pHluorin by extending it at the 5’ end with the first 24 bp of comGA. The new version, which showed an approximate 40% increase in fluorescence intensity, was expressed from developmental phase-specific, native promoters of B. subtilis that are specifically active during vegetative growth on glucose (PptsG) or during sporulation (PspoIIA, PspoIIID and PsspE). Our results show strong, compartment-specific expression of IpHluorin that allowed accurate pHi measurements of live cultures during exponential growth, early and late sporulation, spore germination, and during subsequent spore outgrowth. Dormant spores were characterised by an internal pH of 6.0 ± 0.3. Upon full germination the internal pH rose dependent on the medium to 7.0-7.4. The presence of sorbic acid in the germination medium inhibited a rise in the intracellular pH of germinating spores and inhibited germination. Such effects were absent when acetic was added at identical concentrations.